Correlation between structural and optical properties of surfactant assisted sol-gel based mesoporous SiO2-TiO2 hybrid nanoparticles for pH sensing/optochemical sensor - Islam, S. (Elsevier, 2016)
The correlation between structural and optical properties of surfactant-assisted hybrid thin films deposited by sol-gel method has been studied. The samples prior and after heat treatment were characterized by analytical instrumental techniques like field emission scanning electron microscope (FE-SEM), energy dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), X-ray diffraction (XRD), transmission electron microscope (TEM) and UV-vis spectroscopy. Microscopic results indicate that the inorganic nanoparticles are much smaller in the presence of surfactant than in the pure hybrid film, and the shape of the inorganic particles and compatibility with surfactant vary at a low-temperature of 100 °C. FE-SEM study confirms grain size within 12-20 nm range that exhibit regular morphology with large pores without any cracks. EDX analysis verify stoichiometric formation of nanocomposite. XRD of the films reveal amorphous to crystalline anatase titania phase after annealing at low-temperature of 100 °C. The FTIR confirms the bond linkage between silica, titania and surfactant molecules. The refractive index of 1.48, with thickness 138 nm and porosity 73% of the films are measured with spectroscopic ellipsometry. Band-gap of 3.8 eV is obtained from the absorption of UV-vis spectroscopy. UV-vis spectroscopy reveals that the prepared matrix shows good response at pH 12 with 96.19% repeatability without leaching and has potential as optochemical sensor with fast response time.